2018
DOI: 10.4253/wjge.v10.i8.130
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between endoscopic sphincterotomy vs endoscopic sphincterotomy associated with balloon dilation for removal of bile duct stones: A systematic review and meta-analysis based on randomized controlled trials

Abstract: AIMTo compare gallstones removal rate and incidence of bleeding, pancreatitis, use of mechanical lithotripsy, cholangitis and perforation between isolated sphincterotomy vs sphincterotomy associated with balloon dilation of papilla in choledocholithiasis through the meta-analysis of randomized clinical trials.METHODSWe conducted a systematic review according to the PRISMA guidelines. Literature search was restricted to randomized controlled trials (RCTs) on MedLine, Cochrane Library, LILACS, and EMBASE databas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Literature review shows that DASE-related bleeding is statistically less frequent than occurs in patients treated with EST alone[ 13 , 17 ]. This was confirmed in a recent meta-analysis, which highlighted how post-ERCP bleeding is significantly more frequent in patients treated with complete EST compared to DASE (3.4% vs 1.9%, P = 0.02)[ 28 ]. Of note, the systematic review by Kim and colleagues published in 2013 showed that bleeding related to maximal EST and papillary large balloon dilatation was slightly higher in respect to patients treated with EST alone, whereas there were no differences between patients treated with papillary dilation combined with partial or no EST[ 27 ]; these data proved once again that bleeding is strictly related to sphincterotomy and its extension.…”
Section: Complicationsmentioning
confidence: 64%
“…Literature review shows that DASE-related bleeding is statistically less frequent than occurs in patients treated with EST alone[ 13 , 17 ]. This was confirmed in a recent meta-analysis, which highlighted how post-ERCP bleeding is significantly more frequent in patients treated with complete EST compared to DASE (3.4% vs 1.9%, P = 0.02)[ 28 ]. Of note, the systematic review by Kim and colleagues published in 2013 showed that bleeding related to maximal EST and papillary large balloon dilatation was slightly higher in respect to patients treated with EST alone, whereas there were no differences between patients treated with papillary dilation combined with partial or no EST[ 27 ]; these data proved once again that bleeding is strictly related to sphincterotomy and its extension.…”
Section: Complicationsmentioning
confidence: 64%
“…This technique is relatively safe, however careful evaluation of radiological imaging is mandatory since the diameter of the balloon should not exceed the diameter of the distal bile duct and the EPLBD should not be performed when the distal bile duct is not dilated to avoid the risk of perforation[ 2 ]. A recent meta-analysis on EST plus EPLBD versus EST alone for choledocholithiasis showed fewer overall complications (OR = 0.53, 95%CI: 0.33-0.85, P = 0.008) and decreased use of mechanical lithotripsy (OR = 0.26, 95%CI: 0.08-0.82, P = 0.02) in the EST plus EPLBD group, with no significant differences regarding adverse events and stone clearance[ 3 ]. More recently, Hakuta et al[ 4 ] evaluated short- and long-term outcomes of EPLBD without EST and EPBD for large stones; in a propensity-matched analysis involving 44 patients, EPLBD without EST was significantly more effective for removal of large stones but showed worse long-term outcomes compared to EPBD.…”
Section: What Has Changed In the Past Few Years?mentioning
confidence: 99%
“…The limits of standard diagnostic work up can lead to multiple, repeated procedures in order to obtain a diagnosis, which means extended time from clinical presentation to treatment (reducing the probability of a curative resection in patients with malignancy), but also increased risk for procedurerelated adverse events (AEs) [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%